2022
DOI: 10.3390/ijerph19031701
|View full text |Cite
|
Sign up to set email alerts
|

Challenging “The Hands of Technology”: An Analysis of Independent Living for People with Intellectual Disabilities

Abstract: Technology has been holding out the promise of facilitating greater autonomy and improving care for people in a situation of dependency. This trend is expected to grow and this is happening precisely at a time of expansion of the so-called Independent Living paradigm. In this context, however, disability activists are generally suspicious of approaches based on being “left” in the hands of technology. They instead advocate for “subordinating hands” to their ability to decide, a principle that stands in tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Thus autonomy hinges on both liberty (freedom from controlling influences), agency (the capacity for intentional action), and understanding (the ability to understand the content and consequences of alternatives) 25 . In the contemporary discourse of disability, as separated into biological impairment, mental incapacity, and social disability [26][27][28] , autonomy extends beyond traditional notions and has been reconceptualized as the capacity to establish meaningful connections and relationships 28 . In this and other relational definitions, autonomy is "distributed agency", meaning it is dispersed among diverse human and non-human actors interconnected at specific times 29,30 .…”
Section: Autonomymentioning
confidence: 99%
“…Thus autonomy hinges on both liberty (freedom from controlling influences), agency (the capacity for intentional action), and understanding (the ability to understand the content and consequences of alternatives) 25 . In the contemporary discourse of disability, as separated into biological impairment, mental incapacity, and social disability [26][27][28] , autonomy extends beyond traditional notions and has been reconceptualized as the capacity to establish meaningful connections and relationships 28 . In this and other relational definitions, autonomy is "distributed agency", meaning it is dispersed among diverse human and non-human actors interconnected at specific times 29,30 .…”
Section: Autonomymentioning
confidence: 99%
“…Science and technology studies have shown how the capacity to act depends on heterogeneous networks that allow certain modes of individual agency (Callon, 2008). In the case of AC, this involves the articulation of a set of more or less formal meetings with families and users, the formulation of a personal care plan, the provision of formal and informal meeting spaces, the use of furniture catalogues, certain technologies, and so on (Moyà-Köhler & Domènech, 2021; 2022) that allow the person with learning disabilities to emerge as autonomous in the process of thinking (Law, 1999) and taking decisions. In the case of CL, it entails facilitating a nonhospital space, to develop individualized plans, the promotion of community activities, and the training of assistants in the promotion of independent living.…”
Section: Tensions and Escapesmentioning
confidence: 99%